2013
DOI: 10.1016/j.ccr.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-11 Is the Dominant IL-6 Family Cytokine during Gastrointestinal Tumorigenesis and Can Be Targeted Therapeutically

Abstract: Among the cytokines linked to inflammation-associated cancer, interleukin (IL)-6 drives many of the cancer "hallmarks" through downstream activation of the gp130/STAT3 signaling pathway. However, we show that the related cytokine IL-11 has a stronger correlation with elevated STAT3 activation in human gastrointestinal cancers. Using genetic mouse models, we reveal that IL-11 has a more prominent role compared to IL-6 during the progression of sporadic and inflammation-associated colon and gastric cancers. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
389
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(433 citation statements)
references
References 67 publications
18
389
2
2
Order By: Relevance
“…IL11 protein (16) and mRNA (17), along with IL11Ra protein levels are progressively increased with increased endometrial tumor grade (16), which is in line with findings in other tumor types such as ovarian and colorectal (18,19). Studies have reported protumorigenic roles for IL11 in several epithelial cancers, including breast (20) and colorectal cancer (19) and one recent study highlighted a predominant role for IL11 rather than IL6 in mediating gastric cancer (21). We have previously demonstrated that IL11 promotes endometrial cancer cell migration in vitro, via STAT3 (22).…”
Section: Introductionsupporting
confidence: 73%
“…IL11 protein (16) and mRNA (17), along with IL11Ra protein levels are progressively increased with increased endometrial tumor grade (16), which is in line with findings in other tumor types such as ovarian and colorectal (18,19). Studies have reported protumorigenic roles for IL11 in several epithelial cancers, including breast (20) and colorectal cancer (19) and one recent study highlighted a predominant role for IL11 rather than IL6 in mediating gastric cancer (21). We have previously demonstrated that IL11 promotes endometrial cancer cell migration in vitro, via STAT3 (22).…”
Section: Introductionsupporting
confidence: 73%
“…These results indicate the role of COX-2/PGE 2 pathway-induced inflammation in gastric tumorigenesis. In the gastric tumor stroma, proinflammatory cytokines including TNFa, IL1b, and IL11 are expressed and promote tumorigenesis through enhancement of undifferentiated status, recruiting of myeloid-derived suppressor cells and increasing tumor cell survival (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…3 F). Because IL-6 and IL-11 can activate STAT3 (Bollrath et al, 2009;Putoczki et al, 2013), increased pSTAT3 observed in Naip1-6 / tumors might be related to the observed up-regulation of those cytokines. Also consistent with STAT3 activation, downstream targets Mmp9 and Timp1, which can act to enhance tumor growth or invasion (Kim et al, 2012;Shuman Moss et al, 2012), as well as Stat3 itself, were elevated (Fig.…”
mentioning
confidence: 98%